2015
DOI: 10.25159/2520-5293/215
|View full text |Cite
|
Sign up to set email alerts
|

Being in a Dilemma: Experiencing Birth in Zambia

Abstract: numerous publications investigating childbirth in sub-saharan Africa have overlooked the psychological and emotional elements that women experience, in favour of physical dimensions, such as maternal mortality. the aim of this study was to explore childbirth experiences, in order to better understand how women in Zambia experience and give meaning to the phenomenon. An interpretive phenomenological approach was utilised. through purposive sampling methods, fifty birthing women, aged between 16 and 38 years, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…This might be due to marriage being a culturally acceptable practice in Zambia. These findings are similar to Kwaleyela et al [14] in a study titled childbirth experiences of women birthing in Zambia: an interpretive focus phenomenological study had a theme conforming to societal expectations, which revealed the relationship between marriage and childbirth in Zambia. Midwives, 34.6% (37) and nurses, 35.5% (38) made the majority of the respondents (Table 1).…”
Section: Characteristics Of the Respondentssupporting
confidence: 88%
See 1 more Smart Citation
“…This might be due to marriage being a culturally acceptable practice in Zambia. These findings are similar to Kwaleyela et al [14] in a study titled childbirth experiences of women birthing in Zambia: an interpretive focus phenomenological study had a theme conforming to societal expectations, which revealed the relationship between marriage and childbirth in Zambia. Midwives, 34.6% (37) and nurses, 35.5% (38) made the majority of the respondents (Table 1).…”
Section: Characteristics Of the Respondentssupporting
confidence: 88%
“…The association in the provision of preconception care between those with college 12.7% (7); and university 38.5% (20) education was statistically significant (p = 0.003). Similarly, the association in the provision of preconception care between midwives 27% (10), nurses 7.9% (3) and doctors 43.8% (14) was statistically significant (p = 0.02). The association between religious affiliation and provision of preconception care was also statistically significant (p = 0.01).…”
Section: Associations Between Variablesmentioning
confidence: 85%